COMBINATION OF DECIDUAL DENTAL STEM CELL AND PLATELET RICH PLASMA IN FIBROBLAST FORMATION IN THE JAWBONE REGENERATION OF WISTAR RATS - Ade Ismail; Rahmawati Sri Praptiningsih; Muhammad naufal (ODONTO : Dental Journal, 2022)
Background: Orthodontic tooth movement is caused by mechanichal forces that cause pseudo-inflammation with the result that FGF (Fibroblast Growth Factors) was activated. The combination of SHED (Stem Cell From Human Exfoliated Deciduous Theeth) and PRP (Platelet Rich Plasma) hydrogels can affect the formation of fibroblast in the alveolar bone regeneration. The purpose of this study is the effect determination of SHED and PRP hydrogels for fibroblast formation in alveolar bone regeneration in wistar rats.Method: An experimental study was held using post-test only control group design. There were four groups, namely the PRP hydrogel group, the SHED hydrogel group, the SHED and PRP hydrogel group, and the povidone iodine group (n=8) treated with orthodontic tooth movement. Their mandibular tissue was made as histologycal slide, and the FGF expression were observed microscopically with 100x magnification. The data analyzed by ANNOVA and LSD test.Result: There was a significant effect of the combination of SHED and PRP hydrogel in ordering fibroblast in alveolar bone regeneration by ANNOVA test 0.001 (<0.05). This is because SHED and PRP are able to stimulate FGF expression through external stimulation.Conclusion: It concluded that the combination of SHED and PRP hydrogel affected fibroblast formation on alveolar bone regeneration in wistar rats